Selectivity and Effectiveness of Multilevel Wall Traps for Capturing Lobsters (Panulirus Spp) at Laboratory Scale - Abdullah, Agung Sobri; Suharyanto, Suharyanto; Soeboer, Deni Achmad (Journal La Lifesci, 2025)
Krendet, gill nets, and traps are fishing gear commonly used to catch lobsters (Panulirus spp) by Indonesian fishermen, but there are many issues related to the use of non-selective and environmentally unfriendly fishing gear. This laboratory research aims to develop selective and effective lobster capture technology, in line with the implementation of PERMEN KP No. 27 of 2024 regarding lobster management. The data obtained were analyzed using the Independent Sample t-Test to evaluate the differences in selectivity and effectiveness between the HDPE multilevel wall traps and the standard foldable traps in capturing legal-sized lobsters. The analysis results showed that the multilevel wall traps performed better, with a total of 56 lobsters captured, all of which were legal-sized (≥ 200 grams), while the foldable traps only captured 26 legal lobsters and 20 illegal ones, accounting for approximately 43.48% of illegal catches. This shows that the tiered wall trap is more selective and environmentally friendly. In terms of the proportion of legal catches, the use of multilevel wall traps increased the number of legal catches by 77.8% compared to foldable traps, which is highly significant for the sustainability of lobster resources. Statistical tests also show that the average weight of lobsters caught by tiered wall traps is significantly higher, with a mean difference of 173.02 grams (p 0.000) and a 95% confidence interval between 126.99 and 219.04 grams.